2022
DOI: 10.1186/s12888-022-04437-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mortality risk among patients with substance use disorder: an opportunity for proactive patient safety?

Abstract: Background Patients with substance use disorder (SUD) suffer from excess mortality compared to the overall population. This study aims to identify patterns in death rates among patients with SUD visiting a SUD emergency ward and to explore whether this knowledge can be used as input to identify patients at risk and increase patient safety. Methods Hospital visit data to a SUD emergency ward were collected between 2010 and 2020 through medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…This gender-specific variation suggests that males may face greater mortality risk when experiencing mental and behavioral disorders associated with psychoactive substances compared to females. These findings align with a prior analysis conducted by Svensson et al, which revealed that male patients with substance use disorder faced a mortality risk that was 1.41 to 1.59 times higher than their female counterparts [10][11][12][13]. The gender differences in mortality rates highlight the need for gender-sensitive approaches in prevention, early intervention, and treatment strategies targeting substance use disorders.…”
Section: Discussionsupporting
confidence: 87%
“…This gender-specific variation suggests that males may face greater mortality risk when experiencing mental and behavioral disorders associated with psychoactive substances compared to females. These findings align with a prior analysis conducted by Svensson et al, which revealed that male patients with substance use disorder faced a mortality risk that was 1.41 to 1.59 times higher than their female counterparts [10][11][12][13]. The gender differences in mortality rates highlight the need for gender-sensitive approaches in prevention, early intervention, and treatment strategies targeting substance use disorders.…”
Section: Discussionsupporting
confidence: 87%